Pendekatan Feminisme dalam Analisis Cerpen “Kunang-Kunang dalam Bir” Karya Djenar Maesa Ayu - Rauzatul Jannah (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to examine how feminist values ​​are represented in the short story Kunang-Kunang in Bir by Djenar Maesa Ayu. Using descriptive qualitative research methods. Feminist literary criticism allows for in-depth analysis of themes, characters, and symbols related to issues of gender and inequality. In the analysis of this short story, gender inequality, social norms and symbolism were found. The results of this research show women's struggle in facing patriarchal norms and injustice that prevent women from achieving happiness. The symbolism used increases public criticism of ongoing gender inequality. It is hoped that this research can contribute to feminist literary studies and encourage awareness of the importance of women's freedom in making life decisions.